Pengaruh computer anexiety terhadap keahlian dosen dalam penggunaan komputer - Nur Indriantoro (Jurnal Akuntansi dan Auditing Indonesia, 2000)
This study examines the relationship between computer anxiety and skill in end-user computing. The study extends Harrison and Rainer (1992) and Rifa and Gudono (1999) to lecturer in her education. Data from 54 lecturers in private universities at Daerah Istimewa Yogyakarta area, supports the hypothesis thatcomputer anxiety effects negatively skill on end-user computing.